(untitled) (Research, Society and Development, 2026)
Autism Spectrum Disorder (ASD) is classified as a neurodevelopmental disorder that affects not only the child’s development but also family dynamics. This study aimed to analyze, through a qualitative bibliographic approach, the main challenges faced by families of individuals with ASD. Scientific publications and official documents addressing the emotional impacts of diagnosis, barriers to access health and educational services, and coping strategies adopted by families were examined. The findings indicate that the diagnosis triggers emotional and structural reorganization within the family, often associated with caregiver burden. Despite regulatory advances, difficulties remain regarding the effective implementation of public policies and the articulation between services. It is concluded that strengthening support networks, improving professional training, and expanding access to specialized services are essential measures to reduce the social and emotional impacts associated with ASD.